PENINGKATAN KEMANDIRIAN OKUPASIONAL LANSIA MELALUI INTERVENSI AKTIVITAS BERMAKNA BERBASIS KOMUNITAS - Wahyuni, Endang Sri; Arifiati , Retna Febri; Haryanti, Haryanti (Jurnal Indonesia Mengabdi, 2025)
Background: Indonesia’s ageing population demands proactive strategies to preserve older adults’ quality of life, particularly in maintaining occupational independence, which often declines due to physical limitations, social isolation, and inadequate access to community-based rehabilitation. This community service aimed to enhance the understanding and participation of older adults in occupational independence through a culturally grounded, meaningful activity program in Kersan Brintikan Hamlet, Tirtomartani Village, Kalasan Subdistrict, Sleman Regency. Methods: A pre–post-test counselling design was employed with 52 participants (46 older adults and 6 elderly health cadres). The intervention included health screening, morning walking, anti-hypertension exercise, occupational therapy services, and interactive health education using visual media. A structured questionnaire comprising 10 closed-ended items was administered before and after the session to assess changes in knowledge. Results: Most participants were in the pre-elderly age group (64.3%), nearly gender-balanced (48.1% male, 51.9% female), and moderately to highly educated (78.7% senior high school or above). The mean understanding score significantly increased from 4.75 (pre-test) to 9.33 (post-test), while the standard deviation decreased from 1.064 to 0.857, indicating a homogeneous and substantial improvement in comprehension across participants. Conclusion: A participatory, contextually relevant program combining health promotion and meaningful occupational activities effectively enhances awareness of occupational independence among older adults. For sustainability, follow-up sessions, cadre capacity building, and inclusive outreach to older and male elders are recommended to support active ageing in the community.